Farmer’s Income and Allocative Efficiency Analysis in Rice Production in Koto Tangah Subdistrict Padang City - Leovita, Angelia (Perum BULOG, 2023)
The low productivity of lowland rice (Oryza sativa L.) in Koto Tangah District is affecting farmers’ income. The objectives of this research were to analyze : (i) income from lowland rice cultivation, (ii) factors that influence rice production, and (iii) the efficiency of utilization of lowland rice production factors in Koto Tangah District. The method used in this research was quantitative, using probability sampling techniques with proportional random sampling method and 44 respondents were involved. The data analysis techniques used were income analysis, Cobb-Douglas production function, T-test (partial), F-test (simultaneous), coefficient of determination, and efficiency analysis. Based on the survey results, it was known that the total income from lowland rice cultivation in Koto Tangah District was IDR2,607,860.36/average land area/ MT, and lowland rice cultivation was possible with an R/C value of 1.21. The factors that influenced lowland rice production in Koto Tangah District were land area, seeds, and chemical fertilizers, which significantly affected production levels. In contrast, pesticides, labor within the family, and labor outside the family do not significantly affected lowland rice production in Koto Tangah District. Although production factors such as land area, seeds, fertilizers, pesticides, and family labor (TKDK) were still inefficient, non-family labor (TKLK) had almost reached an efficient level.